362 AMBULATORY BLOOD PRESSURE MONITORING IN THE DIALYSIS POPULATION: IS IT ESSENTIAL?. Issue 1 (1st January 2007) - Bilbrew, D.; Islam, N.; Valentine, K.; Fulop, T.; Salem, M.; Flessner, M.; Schmidt, D.
Abstract : Background: Hypertension is endemic in the dialysis population. Nephrologists rely on routine blood pressure (RBP) measurements of predialysis blood pressure (Pre-BP) and postdialysis blood pressure (post-BP) to assess hypertension. Current K-QOQI guidelines recommend target pre-BP and post-BP of 140/90 and 130/80 mm Hg, respectively. The purpose of this study was to assess the relationship of RBP to ambulatory blood pressure (ABP) measurements and to determine the burden of uncontrolled hypertension in our hemodialysis population with ABP measurements. Methods: RBP measurements were made by trained dialysis staff with patients after sitting 5 minutes before and after dialysis. Six RBP measurements were averaged, pre- and postdialysis. ABP was measured between the fifth and sixth RBP measurement over the 44-hour interdialytic period with Spacelab ABP monitors. Mean ± SD BP (mm Hg) using both techniques was compared using the paired t -test. Results: With n = 35, the mean ABP was 135.5 ± 22.8/80.3 ± 15.1. Mean pre-BP averaged 162.6 ± 22.4/88.2 ± 13.9 ( p < .0001), whereas post-BP averaged 148.8 ± 23.8 /80.6 ± 13.4 ( p < .0001 for systolic pressure). The percentage of subjects with a systolic blood pressure greater than goal was 40% for ABP, 84.4% for pre-RBP, and 75.8 for post-RBP. The percentage of subjects with a diastolic greater than goal was 22.9 for ABP, 40.6% for pre-RBP, and 39.4% for post-RBP. Conclusion: ABP demonstrates BP significantly less than either the pre/post dialysis blood pressures. Routine pre/post blood pressures therefore may overestimate the true burden of hypertension in this patient population. When blood pressure is measured using an average of ABP, a significantly lower percentage of participants were above blood pressure targets.